Cadaveric Bilateral Transhumeral Upper Limb Transplantation: Journey to the Next level - Kumar S Dinesh; Abhinav Aggarwal; Ravi Kumar Chittoria; Friji Meethale Thiruvoth; Devi Prasad Mohapatra; Vinayak Chavan; Saurabh Gupta; Chirra Likhitha Reddy (Indian Journal of Plastic Surgery, 2020)
Organ transplant has, arguably, been the pinnacle of the advancement in medical science so far and vascularized composite allotransplantation has been the most recent addition to it. The scope of vascularized tissue allotransplantation has been widening with each passing day and more and more reports regarding the safety and efficacy of the procedure have been described. Due to the limited available literature on the management of the complications and implications of the hand transplant, the importance of each report on the procedure is paramount. A mid-arm allotransplant is a challenge in terms of expected motor recovery, and many controversies exist over the efficacy of the procedure altogether. Moreover, our case was complicated by a long ischemia time due to logistic reasons. We share our experience of a transhumeral upper limb allotransplantation, the complications associated with it along with the early postoperative results at 10 months follow up.